Emotional Labor in Service Work: Its Impact on Satisfaction and Performance - Berilian Ayu Kusuma (PT. Anagata Sembagi Education, 2026)
Emotional labor has become a critical component in service-oriented organizations, where employees are required to regulate their emotions to meet organizational expectations and enhance customer satisfaction. While emotional labor can improve service quality and performance, it also poses risks to employee well-being, particularly when poorly managed. This study aims to analyze the impact of emotional labor strategies—surface acting, deep acting, and genuine acting—on employee satisfaction and performance. The research adopts a qualitative approach using a systematic literature review and document analysis of recent peer-reviewed studies. Data are analyzed through thematic and qualitative content analysis to identify key patterns related to emotional regulation, employee well-being, and performance outcomes. The findings reveal that surface acting leads to emotional exhaustion, burnout, and reduced job satisfaction and performance, whereas deep acting and genuine acting contribute to higher satisfaction, lower stress, and improved service performance. The discussion highlights the importance of organizational support, emotional intelligence, and service climate in moderating these effects. In conclusion, effective management of emotional labor requires a shift toward human-centered practices that promote authentic emotional engagement and sustainable performance..